Effect of Ice Temperature and Air Controlling Ice Temperature(ACIT) on Quality of Winter Jujube - Song Jianfei; Liu Bin; Wu Zijian; Wang Chao (Zhileng xuebao)
In order to study the effect of ice temperature and ACIT storage on quality of the winter jujube, we put the jujube in the cold precooling room for 24 hours, and divided them into three levels(0 level,1 level,2 level) according to the different maturity. The jujubes of different levels were then placed under the ice temperature (-2.4 ℃) and ACIT storage conditions (-2.4 ℃, 5% O2 concentration and 0.5% CO2 concentration )，and the weight-loss rate ,flesh hardness, peel hardness, brittleness, soluble pectin content and Vc content of the jujube during storage were measured. The results show that ACIT storage condition can effectively delay the decay of the winter jujube, during the whole process of the storage, three grades jujube under air conditioning ice temperature is significantly better than that of ice temperature storage in terms of weight loss rate, brittleness and soluble pectin content and Vc content（P＜0.05）; for peel hardness, 1 grade jujube under ACIT is better than that under ice temperature storage, 0 grade and 2 grade jujube under ice temperature are better than that under ACIT; for flesh hardness, we can get that ice-temperature storage condition has a better effect than ACIT which is better than the common controlled atmosphere storage（P＜0.05）; the quality of the low red index jujube is relatively good.